The role of blockhain in creating cryptocurrency - Cvijić Vasilije M. (Savez inženjera i tehničara Srbije, 2021)
The main carrier of the cryptocurrency system is blockchain. The paper will explain the differences between tokens and coins, the role of miners in the cryptocurrency system, forks, how a consensus mechanism is achieved. The protocols in use will also be discussed. Due to technical similarities, a blockchain was compared with Bitcoin, which provides an excellent reference point. The paper also presents the practical application of blockchain in the form of smart contracts. The paper will propose the stages of development of own cryptocurrency, from the very beginning, where the purpose of existence is defined, through the selection of technical solutions, until the finalization where marketing and commercial aspects play a crucial role for success, with guidelines for legal aspects.